A CONTRIBUIÇÃO DO CURSO DE GESTÃO PÚBLICA DA UNIVERSIDADE FEDERAL DO PAMPA - UNIPAMPA PARA A MODERNIZAÇÃO DA ADMINISTRAÇÃO PÚBLICA EM SANTANA DO LIVRAMENTO/RS - Raquel Duarte Preste (Universidade Federal de Santa Catarina, 2016)
This study aimed to identify the Contribution of the under graduation in public management of the Universidade Federal do Pampa - UNIPAMPA to the Modernizat ion of public administration in the city of Santana do Livramento/RS. For the development of this research was used the case study method performed in UNIPAMPA. Data collection was made through semi - structured interviews and analyzes were developed from a qualitative bias. As a result it was find that, today the contribution of the under graduation in public management UNIPAMPA has been essential to seek improvements in the proving services in the Municipality of Santana do Livramento, to be the institution the most benefited for academic production in the course of Public Management, as with the use of graduates. The urgent need to qualify and to train the public managers of the city, has increased the interest in the continued training of local public sect or manager, and today UNIPAMPA offer the course of Specialization on Public Management also.